Genetic variability analysis for yield traits in sponge gourd (Luffa cylindrica L.) in arid environment - Gantayat, Ankit; Choudhary, B R; Yadav, P K; Ram, Chet; Sharma, Yogesh; Kumar, Naresh; Chaubey, T; Singh, D K (Current Horticulture, 2025)
The genetic variability, heritability, and genetic advance for 12 yield and yield contributing traits were analyzed in 26 sponge gourd genotypes. The study examined genetic variability in sponge gourd genotypes, revealing significant differences across all traits. A broad range of variation was observed for key traits, including total marketable fruit yield, fruit weight, and days to first fruit harvest. The phenotypic coefficient of variation (PCV) was higher than the genotypic coefficient of variation (GCV), indicating the substantial influence of environmental factors on trait expression. High heritability and genetic advance were observed for traits like fruit diameter and marketable fruit yield, suggesting the predominance of additive gene action. These findings indicate that traits such as fruit yield can be enhanced through selection, while traits with lower genetic advance may benefit from hybridization and other breeding approaches.